Modelo de selección de personal por competencia para las Cooperativas de Ahorro y Crédito de la ciudad de Latacunga en el área comercial - Chacha Vaca, Diana Paulina (2017)
Currently financial institutions focus on the effectiveness of the basic processes at the area of Human Talent, part of which is the selection of personnel. This research aims to develop the competency selection model for the credit unions of the city of Latacunga, taking as reference the commercial area, the reason for this proposal is the outdated staff Administrative, the same that does not allow a good decision when filling a vacant position, this objective gives compliance through the use of bibliographic research analyzing the different models that exist according to several authors, being the most admissible the selection of personnel by competition The same that consists of techniques and tools that help the deepest evaluation of the individual through it can be predicted the performance that will have the applicant in case of being hired. As well as using descriptive research for which a questionnaire is designed for the Heads of Human Talent of the financial sectors, the tabulation of the surveys determines the selection processes, the ideal profile, selection failure, staff turnover Of banks and cooperatives, concluding that the Human Talent departments of the banking sector, are governed by the competition selection model, to fill a vacant position, thus being a guarantee for the application of the proposal, while in most cooperatives there is no An adequate selection process, there is a greater rotation of personnel and low work performance, with the selection model for competition that we present today, we intend to meet the needs raised by the Human Talent department by recruiting suitable and qualified personnel that contribute to the fulfillment of Goals and objectives, since a good selection of personnel in the future will be reflected in the success of the company.